Design thinking for the greater good : innovation in the social sector - Liedtka, Jeanne; Salzman, Randy; Azer, Daisy (Columbia Business School publishing., 2017)
Through ten stories of struggles and successes in social sector organizations, Design Thinking for the Greater Goods shows how collaborative creativity can shake up even the most entrenched bureaucracies-and provide a practical roadmap for readers to implement these tools. This book will help today's leaders in their pursuit of creative solutions.- Resumé vydavatel